Student online marketplace for university community - Mohd Fahmi Ismail; Maslina Abdul Aziz; Fatin Nur Syuhada Mohd Nor; Syaripah Ruzaini Syed Aris; Suzana Zambri (Institute of Advanced Engineering and Science, 2020)
This research presents student online marketplace for university community. In this study, we identify current issues faced by university students while starting their business. Based on the preliminary investigation, it was found out that there are a number of students doing part-time jobs and doing business to support their living expenses. There are varieties of businesses and services offered among students especially students staying in colleges. However, the main problem faced by students either as the buyer or the seller is there is no business platform to promote their products or services. Al-so, there is a lack of information regarding the business or services since most communications are done through h instant messaging apps such as WhatsApp and social media. By having a student online marketplace, the exchange of goods and services take place by having buyers and sellers being in contact with one another. This student online marketplace also helps small businesses to boost their sales, encourage new business start-up and inspire students who have business idea to help them to kick-start their business. Students are able to perform their business in a safe and secure environment.